Management of perioperative thyrotoxicosis – what to do when standard therapy is contraindicated or fails? - Tian, Kristy; Liang, Trilene; Yew, Jielin; Chng, Chiaw-Ling (Frontiers in Endocrinology, 2024)
Background Current guidelines recommend that hyperthyroid patients should be rendered euthyroid prior to surgical procedures. These guidelines rely heavily on the use of ATDs as the primary medication, and do not give recommendations for patients who have contraindications to ATDs, or for whom standalone ATD treatment is inadequate. Objectives To evaluate the efficacy and safety of adjunctive pharmacological therapy and/or therapeutic plasma exchange (TPE) in the perioperative management of patients with thyrotoxicosis who were intolerant to ATD or for whom standalone ATD therapy was inadequate to achieve euthyroidism prior to surgery. Methods A comprehensive search of MEDLINE, Google Scholar, Embase and CENTRAL up to 31 December 2023 retrieved 12,876 records. After screening titles, abstracts and full manuscripts, 16 reports were enrolled. The study quality was evaluated using the Newcastle-Ottawa Scale (NOS). Results Patients were primarily female (78.5%), aged between 35 and 52 years. The predominant thyroid condition was Graves’ disease (89.7%). Majority underwent thyroidectomy (99.3%). Patients treated pre-operatively with 2nd line pharmacotherapy with/without therapeutic plasma exchange (TPE) underwent surgery safely with no reports of perioperative thyroid storm. Pre-operative treatment achieved mean percentage reduction of free thyroxine and free triiodothyronine levels of 52.6 ± 8.2% and 68.1 ±9.3 % respectively. One study reported a patient who suffered from myocardial infarction and tachyarrhythmia and subsequently demised. Conclusion Preoperative management of hyperthyroidism with second line pharmacotherapy and/or TPE can be effectively and safely implemented in patients with intolerance to or ineffective treatment with ATDs. The treatment modalities were generally safe, though some complications were observed.